Analyzing the Clinical and Economic Impact of Cesarean Delivery on Maternal and Infant Outcomes - Kwakyepeprah, Mary (Université d'Ottawa / University of Ottawa, 2017)
Background: Current cesarean delivery (CD) rates in many industrialized countries are well above the recommended rates. Objective: The overall goal of this thesis was to identify sources for unnecessary CD. Specific objectives were to: 1) analyze the leading indications for CD and their associations with neonatal outcomes; 2) compare adverse birth outcomes between elective primary cesarean delivery (EPCD) and trial of labor after vaginal birth (TOLAV), and between elective repeat cesarean delivery (ERCD) and trial of labor after cesarean birth (TOLAC); and 3) assess the cost-effectiveness of ERCD and TOLAC. Methods: A retrospective cohort study was conducted. Leading indications for CD were analyzed and risks of neonatal outcomes between “soft” indications and “hard” indications were compared first, using 2006 to 2013 Better Outcomes and Registry Network Ontario data. A pair of analyses: comparing risks of adverse birth outcomes between EPCD and TOLAV and between ERCD and TOLAC, were then conducted using United States 2005 to 2010 birth registration data. Analysis were performed using logistic regression and propensity score matching models. Finally, a cost-effectiveness analysis between ERCD and TOLAC was performed. Results: The single largest contributor for overall CD was ERCD (34.3%) and for primary CD was dystocia (31.9%) in Ontario. Compared with infants of mothers with CD for “hard” indications, the risks of Apgar score <7 at 5 minutes for infants of mothers with CD for non-reassuring-fetal-status was increased, while the risks of Apgar score <7 at 5 minutes and neonatal death for infants of mothers with ERCD and dystocia were decreased. Compared with infants of mothers who underwent TOLAV, infants of mothers who underwent EPCD were more likely to require antibiotics and ventilation support, but less likely to have birth injury. On the other hand, compared with infants of mothers who underwent TOLAC, infants of mothers who underwent ERCD were less likely to require antibiotics and ventilation support. ERCD was similar to the TOLAC birth option in terms of cost effectiveness. Conclusions: Tight up criteria for “soft” indications such as labor dystocia could result in substantial reduction in CD without harming the infants.
Keywords: Cesarean delivery; Infant outcomes; Indications; Cost effectiveness analysis; Cohort study; Propensity score matching